Genetic exploration of interactive domains in RNA polymerase II subunits. - Martin, C (1990)
The two large subunits of RNA polymerase II, RPB1 and RPB2, contain regions of extensive homology to the two large subunits of Escherichia coli RNA polymerase. These homologous regions may represent separate protein domains with unique functions. We investigated whether suppressor genetics could provide evidence for interactions between specific segments of RPB1 and RPB2 in Saccharomyces cerevisiae. A plasmid shuffle method was used to screen thoroughly for mutations in RPB2 that suppress a temperature-sensitive mutation, rpb1-1, which is located in region H of RPB1. All six RPB2 mutations that suppress rpb1-1 were clustered in region I of RPB2. The location of these mutations and the observation that they were allele specific for suppression of rpb1-1 suggests an interaction between region H of RPB1 and region I of RPB2. A similar experiment was done to isolate and map mutations in RPB1 that suppress a temperature-sensitive mutation, rpb2-2, which occurs in region I of RPB2. These suppressor mutations were not clustered in a particular region. Thus, fine structure suppressor genetics can provide evidence for interactions between specific segments of two proteins, but the results of this type of analysis can depend on the conditional mutation to be suppressed.